An Analytical Study for Preserving U.S. Army Barracks Constructed between 1880 and 1940 - Phillips, David John (My University, 2000)
This thesis studies the development of the U.S. Army barracks as a major type of building constructed on military reservations from 1880 through 1940. It includes an analytical study of those structures built between 1880 and 1915 and those between 1920 and 1940 and raises the question, have they become significant enough for preserving? In order to determine the significance of these barracks, one has to study the organization of the Army, and how the barracks are designed and built and what a soldier did in the barracks. Barracks are significant buildings on every Army installation as their architectural style has usually set the tone for the design of the rest of the installation. The location of the barracks, usually along the edge of the parade field, also indicates the significance of these structures. Two economic analysis case studies show the cost benefits of preserving the structures. One analysis of a barracks at Fort McNair, Washington, DC, describes the benefits of rehabilitating a 1903 barracks into a barracks that supports the current Department of Defense design standards. The second analysis looks at a 1934 barracks at Fort Lewis, Washington. This structure was rehabilitated into administrative offices for employees of the installation staff. In preserving these barracks, they must be documented. Less than 10% of the existing structures are listed on the National Register. The Army should establish a formal program for identifying and inventorying all those barracks that remain, including those not under the Army's control. The Army should evaluate all of the identified and inventoried barracks for determination of eligibility for listing on the National Register of Historic Places. Finally, the Army should submit those barracks that are eligible for listing to the National Register of Historic Places as a thematic nomination. The National Register listing then can be used as a planning tool, along with the economic analysis models provided in this paper as a starting point to manage these barracks and make appropriate preservation decisions department wide.
Keywords: Military architecture; Historic preservation -- Theses